2017
DOI: 10.1016/j.ijcard.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of ICAM-1 in aldosterone-induced atherosclerosis

Abstract: Objective Elevated aldosterone is associated with increased risk of atherosclerosis complications, whereas treatment with mineralocorticoid receptor (MR) antagonists decreases the rate of cardiovascular events. Here we test the hypothesis that aldosterone promotes early atherosclerosis by modulating intercellular adhesion molecule-1 (ICAM-1) expression and investigate the molecular mechanisms by which aldosterone regulates ICAM-1 expression. Methods and Results Apolipoprotein-E (ApoE)−/− mice fed an atheroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 55 publications
(62 reference statements)
3
65
0
4
Order By: Relevance
“…ICAM‐1 mediates T‐cell/T‐cell, T‐cell/target cell and T‐cell/B‐cell interactions in addition to its role in the adhesion of inflammatory cells to the vascular endothelium, which facilitates the endothelial transmigration of leucocytes, an important step in the formation of atheroma plaques. Likewise, the chronic elevation of this molecule can involve a situation linked to cardiovascular risk because of the proatherogenic milieu . Reversing this situation, as can be done after surgery, could be an important preventive factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICAM‐1 mediates T‐cell/T‐cell, T‐cell/target cell and T‐cell/B‐cell interactions in addition to its role in the adhesion of inflammatory cells to the vascular endothelium, which facilitates the endothelial transmigration of leucocytes, an important step in the formation of atheroma plaques. Likewise, the chronic elevation of this molecule can involve a situation linked to cardiovascular risk because of the proatherogenic milieu . Reversing this situation, as can be done after surgery, could be an important preventive factor.…”
Section: Discussionmentioning
confidence: 99%
“…22 We noted an increase in the values of ICAM-1 in children with because of the proatherogenic milieu. 23 Reversing this situation, as can be done after surgery, could be an important preventive factor.…”
Section: Discussionmentioning
confidence: 99%
“…2008), a necessary step for cardiac leukocyte infiltration and that aldosterone‐induced vascular inflammation in atherosclerosis requires ICAM‐1 (Marzolla et al. 2017). Moreover, we and others have recently demonstrated that ICAM‐1 is necessary for T‐cell recruitment to the heart (Salvador et al.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Marzolla et al. 2017). We recently showed using the TAC model, that ICAM‐1 is necessary for recruitment of T cells and proinflammatory monocytes to the heart in response to pressure overload and that this mechanism is necessary for progression to systolic dysfunction and HF (Nevers et al.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The vascular inflammation documented after MR activation in the endothelium is associated with increased expression of the adhesion molecules, intercellular adhesion molecule 1 (ICAM-1) 11 and vascular cell adhesion molecule 1 (VCAM-1). 13 The increased expression of adhesion molecules may facilitate leucocyte infiltration, thus amplifying the inflammatory response in the kidney. 13 The increased expression of adhesion molecules may facilitate leucocyte infiltration, thus amplifying the inflammatory response in the kidney.…”
Section: Mr Activation In Endothelial Cells (Ecs) Increases Oxidatimentioning
confidence: 99%